Utilisation of health services and the poor: deconstructing wealth-based differences in facility-based delivery in the Philippines - Andrew Hodge; Sonja Firth; Raoul Bermejo; Willibald Zeck; Eliana Jimenez-Soto (BMC, 2016)
Abstract Background Despite achieving some success, wealth-related disparities in the utilisation of maternal and child health services persist in the Philippines. The aim of this study is to decompose the principal factors driving the wealth-based utilisation gap. Methods Using national representative data from the 2013 Philippines Demographic and Health Survey, we examine the extent overall differences in the utilisation of maternal health services can be explained by observable factors. We apply nonlinear Blinder-Oaxaca-type decomposition methods to quantify the effect of differences in measurable characteristics on the wealth-based coverage gap in facility-based delivery. Results The mean coverage of facility-based deliveries was respectively 41.1 % and 74.6 % for poor and non-poor households. Between 67 and 69 % of the wealth-based coverage gap was explained by differences in observed characteristics. After controlling for factors characterising the socioeconomic status of the household (i.e. the mothers' and her partners' education and occupation), the birth order of the child was the major factor contributing to the disparity. Mothers' religion and the subjective distance to the health facility were also noteworthy. Conclusions This study has found moderate wealth-based disparities in the utilisation of institutional delivery in the Philippines. The results confirm the importance of recent efforts made by the Philippine government to implement equitable, pro-poor focused health programs in the most deprived geographic areas of the country. The importance of addressing the social determinants of health, particularly education, as well as developing and implementing effective strategies to encourage institutional delivery for higher order births, should be prioritised.